An Investigation on the Use of Interaction Design Patterns in Brazilian Government Mobile Information Systems - da Silva, Leonardo Filipe; Freire, André Pimenta (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2020)
In the field of e-government, the use of mobile information systems is gaining space, driven by the ubiquity of the Internet and mobile devices. Interaction design patterns are recurring solutions to common design problems that become increasingly relevant through the contributions made by developers and consequently, users. They are based on proven and frequently used solutions. Despite the existence of a large number of interaction design patterns for mobile systems, there is little knowledge regarding the extent to which governmental apps have employed these solutions, commonly found in commercial apps, to enhance the apps for citizens. This paper presents an evaluation of a sample of 27 Brazilian federal government mobile information systems against a set of 76 interactive design patterns. Our goal was to identify implemented patterns and frequent practices across apps. The results showed that the government’s mobile information systems had a low level of employment of the interaction design patterns analyzed. Applications often implemented strategies for designing very elementary user content, or others linked to input, navigation, or actions. Users who can recognize patterns commonly used in other interfaces may end up having their interaction impaired by the lack of recognition of design solutions commonly present in other apps. Following elements from the Pattern Theory by Christopher Alexander, not observing patterns may be an indicator of the lack of concern with making governmental information systems a more “nurturing” environment to citizens, which may cause lower acceptance of such systems. The analysis of interaction design patterns made in this study can help government agencies to focus on interface components that rely on standard, user-recognizable patterns. These practices can provide users with more familiar ways of using governmental services in mobile systems.